Cover Feature: A Route toward (Aminomethyl)cyclopentadienide Ligands and Their Group 4 Metal Complexes (Eur. J. Inorg. Chem. 34/2018). Issue 34 (31st August 2018) - Bonnin, Quentin; Wong, Sook‐Yen; Balan, Cédric; Comte, Virginie; Malacea, Raluca; Penouilh, Marie‐José; Richard, Philippe; Kehr, Gerald; Normand, Adrien T.; Erker, Gerhard; Le Gendre, Pierre
Abstract : The Cover Feature shows (aminomethyl)cyclopentadienide ligands embedded in the sidewalk of Hollywood Boulevard. This work describes the synthesis of these ligands whose key step is the nucleophilic substitution of sodium cyclopentadienide onto Katritzky's (benzotriazolyl) compounds. This route enables the introduction of bulky and basic amines separated from the cyclopentadienyl ring by a methylene spacer and opens the way to a series of discrete early metallocene derivatives with a pendant amine arm. A representative metallocene complex strolls down the Hollywood Walk of Fame. More information can be found in theFull Paper by G. Erker, P. Le Gendre et al.